GOVERNMENT GOVERNANCE IN THE INDUSTRIAL REVOLUTION ERA 4.0 - Ismail Ismail (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
The concept of Industry 4.0 is one of the topics discussed a lot for researchers and academic practitioners. This article presents and discusses the opportunities and challenges of Revolution Industry 4.0 in governance in Indonesia. The era of Industrial Revolution 4.0 brought the consequence of increasing demands for accountability and transparency of government organizations and high and fast responsiveness, this brought about a change in the organizational design paradigm. Therefore, government organizations must carry out major reforms to be able to successfully carry out their duties and functions in the current era of the Industrial Revolution 4.0. The 4.0 industrial revolution not only brings great benefits but also challenges.